Characterization of T-Bet and Eomes in Peripheral Human Immune Cells - Knox, James J.; Cosma, Gabriela L.; Betts, Michael R.; McLane, Laura M. (Frontiers in Immunology, 2014)
The T-box transcription factors T-bet and Eomesodermin (Eomes) have been well defined as key drivers of immune cell development and cytolytic function. While the majority of studies have defined the roles of these factors in the context of murine T-cells, recent results have revealed that T-bet, and possibly Eomes, are expressed in other immune cell subsets. To date, the expression patterns of these factors in subsets of human peripheral blood mononuclear cells beyond T-cells remain relatively uncharacterized. In this study, we used multiparametric flow cytometry to characterize T-bet and Eomes expression in major human blood cell subsets, including total CD4+ and CD8+ T-cells, γδ T-cells, invariant NKT cells, Natural Killer (NK) cells, B-cells, and dendritic cells. Our studies identified novel cell subsets that express T-bet and Eomes and raise implications for their possible functions in the context of other human immune cell subsets besides their well-known roles in T-cells.